PENDEKATAN HALAQAH DALAM KONSELING ISLAM - Manah Rasmanah (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Islamic counseling as a science is still at the stage of formulation and research, and therefore still needed various scientific studies to formulate various Islamic view of man and all its problems. The most important thing in the formulation of the theory is a reconstruction of the theory of rearranging various viewpoints according to the beliefs held This paper aims to describe the social psychological dimensions contained in halaqah, function and mechanism halaqah in counseling. In these theme are intended to reconstruct the theory of halaqah as a model / approach in Islamic counseling. Psychologically halaqah has many psychological elements that form the basis for placing halaqah as one approaches the Islamic counseling. That dimension is the dimension of catharsis, the ability to deal with anxiety, problem solving, insight, self-control, togetherness, distraction and therapeutic environment. Halaqah as counseling approach has a preventive function (prevention), curative (healing), reservatef (maintenance) and developmental (development). While the process of counseling halaqah through internalization mechanism consisting of three stages of the study groups / tranformation, of calendar / transaction and tanfidz / transinternalisasi.